2020
DOI: 10.1097/hs9.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

A Journey Through Myeloma Evolution: From the Normal Plasma Cell to Disease Complexity

Abstract: The knowledge of cancer origin and the subsequent tracking of disease evolution represent unmet needs that will soon be within clinical reach. This will provide the opportunity to improve patient's stratification and to personalize treatments based on cancer biology along its life history. In this review, we focus on the molecular pathogenesis of multiple myeloma (MM), a hematologic malignancy with a well-known multi-stage disease course, where such approach can sooner translate into a clinical benefit. We des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 160 publications
1
14
0
Order By: Relevance
“…25 Indeed, accumulating evidence suggests that changes in clonal substructure can be used to monitor SMM before end-organ damage develops. 18,30 Genomic events associated with SMM progression include translo-overall survival in one of the two studies, for some patients with higher-risk SMM treated with lenalidomide ± dexamethasone, raising the question of whether such an approach should be considered a new standard of care. In this paper, experts from the European Myeloma Network describe current biological and clinical knowledge on SMM, focusing on novel insights into its molecular pathogenesis, new prognostic scoring systems proposed to identify SMM patients at higher risk of early transformation, and updated results of completed or ongoing clinical trials.…”
Section: New Insights Into the Molecular Pathogenesis Of Smoldering Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…25 Indeed, accumulating evidence suggests that changes in clonal substructure can be used to monitor SMM before end-organ damage develops. 18,30 Genomic events associated with SMM progression include translo-overall survival in one of the two studies, for some patients with higher-risk SMM treated with lenalidomide ± dexamethasone, raising the question of whether such an approach should be considered a new standard of care. In this paper, experts from the European Myeloma Network describe current biological and clinical knowledge on SMM, focusing on novel insights into its molecular pathogenesis, new prognostic scoring systems proposed to identify SMM patients at higher risk of early transformation, and updated results of completed or ongoing clinical trials.…”
Section: New Insights Into the Molecular Pathogenesis Of Smoldering Multiple Myelomamentioning
confidence: 99%
“…Finally, some practical recommendations for the real-life management of these patients, based on Delphi consensus methodology, are provided. cations between the IGH locus and the MYC oncogene 25,30,31 and accumulation of complex rearrangements. 25,30,32 Last, the activity of mutational processes is different in MGUS/SMM and MM.…”
Section: New Insights Into the Molecular Pathogenesis Of Smoldering Multiple Myelomamentioning
confidence: 99%
“…The concept that SMM is an early stage plasma cell neoplasm, without some of the complexity of active MM [ 72 ], makes it tempting to think that a more intense treatment approach may result in cure of some SMM cases rather than just progression delay, a goal not achievable when treatment is started at the active MM stage [ 73 ]. Consequently, several more intensive treatments are being tested in SMM.…”
Section: Proteasome Inhibitor-based Treatments For Smoldering Myelmentioning
confidence: 99%
“…In the light of the current diagnostic criteria [ 26 ], SMM represents a biologically heterogeneous group of plasma cell neoplasms, with variable risk of progression to symptomatic MM [ 27 ]. Some authors suggest that this heterogeneity might be explained by various SMM stages: early MGUS-like cases, a slowly progressing subtype with relatively low mutation burden requiring more time for additional genetic events for progression, and more advanced MM-like cases, rapidly progressing and carrying most genetic lesions typically observed in MM [ 28 ]. Indeed, the analysis of paired samples obtained before and after progression of SMM to MM showed that high-risk SMM does not differ genetically from MM and therefore requires only time to meet clinical diagnostic criteria of symptomatic MM [ 29 ].…”
Section: Natural History Of Disease Evolution In Multiple Myelomamentioning
confidence: 99%